Integrated analysis of genes shared between type 2 diabetes mellitus and osteoporosis - Li, Fangyu; Wang, Ying; Cao, Jie; Chen, Qi; Gao, Yuanyuan; Li, Rui; Yuan, Li (Frontiers in Pharmacology, 2024)
The relationship between Type 2 diabetes mellitus (T2DM) and osteoporosis (OP) has been widely recognised in recent years, but the mechanism of interaction remains unknown. The aim of this study was to investigate the shared genetic features and signalling pathways between T2DM and OP.We analysed the datasets GSE76894 and GSE76895 for T2DM and GSE56815 and GSE7429 for OP from the Gene Expression Omnibus (GEO) database to identify shared genes in T2DM and OP, and we constructed coexpression networks based on weighted gene coexpression network analysis (WGCNA). Shared genes were then further analyzed for functional pathway enrichment. We selected the best common biomarkers using the LASSO algorithm and validated the common biomarkers, followed by RT-PCR, immunofluorescence, Western blotting and Elisa to validate the expression of these hub genes in T2DM and OP mouse models and patients.We found that 8506 and 2030 DEGs in T2DM and OP, respectively. Four modules were identified as significant for T2DM and OP using WGCNA. A total of 19 genes overlapped with the strongest positive and negative modules of T2DM and OP. KEGG analysis showed these genes may be involved in pantothenate and CoA biosynthesis, glycosaminoglycan biosynthesis-chondroitin sulfate/dermatan sulfate and renin-angiotensin system signaling pathway. LASSO algorithm calculates the 6 optimal common biomarkers. RT-PCR results show that LTB, TPBG, and VNN1 were upregulated in T2DM and OP. Immunofluorescence and western blotting show that VNN1 is upregulated in the pancreas of T2DM model mice and in the bones of osteoporosis model mice. Similarly, the level of VNN1 in the sera of T2DM，OP and T2DM combined with OP patients was higher than that in the healthy group.Based on WGCNA and LASSO algorithms, We identified shared genes and pathways in T2DM and OP. Pantothenate and CoA biosynthesis, glycosaminoglycan biosynthesis-chondroitin sulfate/dermatan sulfate and reninangiotensin system may be associated with the pathogenesis of both T2DM and OP.Moreover, VNN1 may be potential diagnostic markers for patients with T2DM complicated by OP. This study provides a new perspective for the systematic study of possible mechanisms of combined OP in T2DM.